Selection of Brazilian native turfgrass accessions for establishment by sprigs - da Silva, Stella Áurea Cristiane Gomes; de Albuquerque Filho, João Carlos Cezar; Silva, Simone Santos Lira; de Castro, Ana Cecília Ribeiro; Loges, Vivian (Ornamental Horticulture, 2020)
Researches with Brazilian native species of Axonopus and Paspalum genus have indicated their lawn-use. Thus, this research aimed to evaluate the use of sprigs, which are rhizomes and/or stolons fragments of plants without substrate and with reduced aerial part, as a propagation method for turfgrass establishment. Two experiments were developed. Experiment 1: turfgrass sods (1026 cm²) from Axonopus parodii (AP 01), Paspalum lepton (PL 01) and P. notatum (PN 01 to PN 06) accessions, were fragmented in a straw crushing machine in order to obtain the sprigs. After cleaning the substrate and organic residues from the sprigs, the following variables were analyzed: total number of sprigs; minimum, maximum and average length of the sprigs; standard deviation; number of sprigs shorter than 2 cm, from 2 to 4 cm, and from 4 to 6 cm long. Experiment 2: sprigs from three different length classes were planted and evaluated at 63 days after planting. The commercial variety Zoysia japonica (ZJ 01) was used as a control treatment. The following characters were analyzed: the survival rate of the sprigs, the number of shoots, expansion, soil coverage rate, dry biomass of aerial part, and dry biomass of the roots. Correlations were made among the data obtained. Higher yields were obtained for sprigs shorter than 2 cm and from 2 to 4 cm. All accessions presented better development when established with sprigs longer than 2 cm. The Paspalum notatum accessions PN 01, PN 02, PN 03 and PN 05 could be selected for turfgrass establishment by sprigs propagation.